Application Of Survival Analysis: A Case Study Of The Nelson-Aalen Method In Patients With Kidney Failure - Agung Prabowo; Uni Febriani; Isna Fingky Musita; Valysha Alhamdaniya Rozak Putri (Research Collaboration Community (RCC), 2026)
Survival analysis is a statistical method used to evaluate the time an event occurs, particularly in censored data. In this study, the Nelson-Aalen method was applied to analyze the survival probability of patients with kidney failure based on medical data from Hasanuddin University Hospital. This method was used to calculate the cumulative hazard and survival function of patients. The analysis results showed that the longer a patient was treated, the greater the chance of recovery. The Nelson-Aalen method was considered more efficient in handling small samples compared to other non-parametric methods. This study provides important insights for healthcare practitioners in planning patient care and improving their quality of life.